2009
DOI: 10.1103/physreva.79.053603
|View full text |Cite
|
Sign up to set email alerts
|

Quantum correlated light pulses from sequential superradiance of a condensate

Abstract: We discover an inherent mechanism for entanglement swap associated with sequential superradiance from an atomic Bose-Einstein condensate. Based on careful examinations with both analytical and numerical approaches, we conclude that as a result of the swap mechanism, Einstein-Podolsky-Rosen-type quantum correlations can be detected among the scattered light pulses. © 2009 The American Physical Society

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The phenomenon of optical superradiance is well known for atoms and molecules, being described in numerous publications (see., e.g., books [1][2][3]). Optical superradiance from Bose-Einstein condensed atoms has also been investigated [4]. There also exists spin superradiance produced by spin systems, such as nuclei [5][6][7][8] or magnetic molecules [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of optical superradiance is well known for atoms and molecules, being described in numerous publications (see., e.g., books [1][2][3]). Optical superradiance from Bose-Einstein condensed atoms has also been investigated [4]. There also exists spin superradiance produced by spin systems, such as nuclei [5][6][7][8] or magnetic molecules [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it includes spatial propagation effects, which are crucial for the thorough understanding of condensate superradiance [11] and were not included in Refs. [10,12].…”
mentioning
confidence: 99%
“…Due to the coherent nature of the condensate, successive Rayleigh scattering events are strongly correlated leading to collective superradiant behavior [9][10][11][12]. Moreover, as a result of the cigar shape of the condensate, the gain is largest when the scattered photons leave the condensate along its long axis, in the so-called endfire modes with momenta k ≈ ±k l e z and frequency ω ≈ ω l .…”
mentioning
confidence: 99%
“…The coherent superpositions of vortices of different circulation quantum numbers, especially vortex-antivortex cases [28,29], yield interesting interference effects with potential applications [30,31], such as manipulating the chirality of twisted metal nano-structures [32]. Creation of matter-wave vortex states from a non-rotating BEC by two-photon Raman transition method under paraxial LG and Gaussian (G) pulse is well discussed in literature [27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. In these studies, matter-wave vortex is shown to acquire vorticity equal to the winding number of the LG beam.…”
Section: Creation Of Superposition Of Bec Vortex Statesmentioning
confidence: 99%